2014
DOI: 10.11336/jjcrs.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Corrected FIM effectiveness as an index independent of FIM score on admission

Abstract: Objective: To correct Functional Independence Measure (FIM) effectiveness for low FIM scores to obtain an index independent of FIM score on admission. Methods: A total of 1,101 stroke patients in Kaifukuki rehabilitation wards were studied. They were divided into 13 groups according to the motor FIM score on admission, in 6-point increments. The parameter "A" was derived so that motor FIM effectiveness, calculated as motor FIM gain/(Amotor FIM score on admission), was around 0.65. Results: Motor FIM effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…In addition, a study has shown that mFIM effectiveness cannot correct the low level of outcome when mFIM on admission is in the low range (13-48 points) [22].…”
Section: Characteristics Of the Outcome Prediction Methods In This Studymentioning
confidence: 99%
“…In addition, a study has shown that mFIM effectiveness cannot correct the low level of outcome when mFIM on admission is in the low range (13-48 points) [22].…”
Section: Characteristics Of the Outcome Prediction Methods In This Studymentioning
confidence: 99%
“…. 20 In this study, the sum of five cognitive items was used to assess cognitive function, and bladder and bowel control for motor function. Furthermore, cognitive function of 25 points or more and bladder and bowel control of 5 points or more were classified as independent, and cognitive function of less than 25 points and bladder and bowel control of less than 5 points were classified as nonindependent.…”
Section: Methodsmentioning
confidence: 99%
“…Relationship between motor FIM improvement (corrected motor FIM effectiveness) and age in proximal femoral fractures called the corrected FIM-M effectiveness, which is calculated as [FIM-M gain / (A − FIM-M at admission)] [4]. The value of A, which yielded a corrected FIM-M gain of around 0.65, was estimated as 42, 64, 79, 83, 87, 89, and 91 points (in the case of FIM-M of 13-18, 19-24, 25-30, 31-36, 37-42, 43-48, and 49-90 points at admission, respectively) in stroke patients [4]. The corrected FIM-M effectiveness can be used as an outcome indicator in which the influence of FIM-M at admission is corrected [5].…”
Section: Original Articlementioning
confidence: 99%
“…Corrected FIM-M effectiveness was calculated using the method reported by Tokunaga et al [4]. The average FIM-M effectiveness for 429 patients with an FIM-M score of 31-90 at admission was 0.649 (Fig.…”
Section: Study 2: Corrected Fim-m Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation